Reflections on the Czech Slavistics After the First World War - Jensterle-Doležal, Alenka (Primerjalna književnost, 2025)
This article compares the positivist thought of two Czech professors of Slavic literature in the 1920s: the Slovenian Matija Murko (1861–1952) and the Czech Jan Hanuš Máchal (1855–1939). Comparative literary history, which in the Central European area focused on minor South Slavic literatures, was in its infancy at this time, and comparative literary historians primarily focused on surveying specific literary periods. The focus of this contribution is Murko’s reflections on South Slavic literature in the period of the Reformation and Counter-Reformation in the book Die Bedeutung der Reformation und Gegenreformation für das geistige Leben der Südslaven (1927). I compare his view and methods with a short chapter on the same period in the monumental monograph by Jan Máchal, Slovanské literatury (1922). In the study, I emphasize their comparative methods, interpreting influences, and marking literary currents in this period. Reflections on the literary movements in two national histories were linked to the development of language, and the scholars tried to present social and historical development of that time and place generally. I focus on their approaches to national and supranational literary history and on their interpretation of personalities and literary works in the literary movement
Keywords: comparative literature; Counter-Reformation; Czech Slavic studies; češka slavistika; južnoslovanske književnosti; Máchal, Jan Hanuš; Murko, Matija; Primerjalna književnost; protireformacija; reformacija; Reformation; Slavistika; Slovenian literary historians; slovenski literarni zgodovinarji; South Slavic literatures